Pacific Regionalism and the Polynesian Leaders Group. Issue 2 (4th March 2017) - Iati, Iati
ABSTRACT: In November 2011, the Polynesian Leaders Group (PLG) was formed. The inclusion of Samoa, Tonga and French Polynesia gives it enough political muscle to have some influence on Pacific regionalism, but exactly what this will be is uncertain. Notably, it was formed during a tense period for regionalism; Australia's and New Zealand's disproportionate influence in the Pacific Islands Forum (PIF) and Pacific Islands Forum Secretariat was increasingly being called into question, while Fiji was crowned the chair of the Melanesian Spearhead Group (MSG) even though it was then expelled from the PIF. To date, the PLG's most notable work has been done in relation to climate change, while it also promises to address decolonisation, both of which are pressing issues on the regional agenda. These might be issue-areas where the PLG will make its mark. Another might be in counterbalancing the increasing regional influence of the MSG, which over the past 10 years has been willing to act independently of the PIF and its traditional benefactors: Australia and New Zealand. An examination of when and why the PLG was formed, how its membership is determined, and its position on key regional issues might provide answers about its regional implications.